Risk retention funding arrangements. A framework for a decision-making proces - Wieczorek-Kosmala, Monika (Formy finansowania retencji ryzyka. Ramy procesu decyzyjnego, 2011)
The paper discusses the nature and role of risk retention as a risk management technique. The key types of risk retention are presented, concerning the intention of their application (unplanned and planned risk retention) and the nature of funding arrangements (unfunded and funded risk retention, including pre- and post-loss funding). Furthermore, the paper examines particular funding arrangements that a company may consider for a given risk exposure. For that purpose, the available funding arrangements are classified into traditional and non-traditional. Within non-traditional funding arrangements closer attention is paid to finite risk programs, contingent capital facilities and captives
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 133-147
Keywords: risk retention; risk management; alternative risk transfer